The cytochromes of mitochondria from Tetrahymena pyriformis strain ST - Lloyd, D. (1972)
1. Mitochondria of the obligately aerobic ciliate protozoon, Tetrahymena pyriformis strain ST, are unusual in that they possess a cytochrome oxidase system that does not react with reduced mammalian cytochrome c; the presence of cytochromes a(603)+a(3) is masked in the α-band region of spectra by the broad absorption band of cytochrome a(620). 2. Other haemoproteins present include cytochromes b(560), b(556), c(553) and c(549). 3. The reaction of reduced cytochrome a(3) with CO is reversed by flash photolysis, and in the presence of O(2) the subsequent oxidation of this cytochrome is followed by that of cytochrome a(603). 4. Cytochromes a(620) and b(560) also react with CO and with KCN; the latter cytochrome corresponds with that designated cytochrome o by other workers. 5. The contribution of cytochrome a(603) to difference spectra is revealed by making use of the fact that it does not react with KCN. 6. Cytochrome a(620) is unstable, and its α-absorption band is lost from spectra of mitochondria which have been aged or treated with ultrasound, detergents or organic solvents. 7. Possible pathways of electron transport via the several different terminal oxidases in Tetrahymena mitochondria are proposed.